« Caminè, caminè » : l’écriture du mouvement dans L’Anconitana d’Angelo Beolco, dit Ruzante - Françoise Decroisette (Laboratoire Italien)
Theatre is the place where words and gestures are combined. In the early sixteenth century, Angelo Beolco, better known as Ruzante, created in his stage writing a poetic use of gesture that affirms the increasing omnipotence of the visual over the textual. The Anconitana, an undated comedy full of mysteries, is undoubtedly the play that most clearly demonstrates this increase in the gesture’s power. Beolco personally inscribes his triple function as author, actor and director.